2016
DOI: 10.1016/j.scriptamat.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Grain growth: The key to understand solid-state dewetting of silver thin films

Abstract: To cite this version:P Jacquet, Renaud Podor, J Ravaux, J Teisseire, I Gozhyk, et al.. Grain growth: The key to understand solid-state dewetting of silver thin films. Scripta Materialia, Elsevier, 2016, pp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 21 publications
1
50
0
Order By: Relevance
“…They observed abnormal grain growth of preferentially oriented grains, as soon as they are in contact with the retracting edge of a growing void. Jacquet et al [36] found the dewetting behavior of silver thin films to be dominated by grain growth throughout the different steps they observed in their in situ environmental (E)SEM study. In our recent work [37] we have studied the kinetics and the morphological mechanism of the process of solid-state dewetting of Au thin films by in situ scanning transmission electron microscopy (STEM) in high-angle annular dark field (HAADF) mode.…”
Section: Introductionmentioning
confidence: 99%
“…They observed abnormal grain growth of preferentially oriented grains, as soon as they are in contact with the retracting edge of a growing void. Jacquet et al [36] found the dewetting behavior of silver thin films to be dominated by grain growth throughout the different steps they observed in their in situ environmental (E)SEM study. In our recent work [37] we have studied the kinetics and the morphological mechanism of the process of solid-state dewetting of Au thin films by in situ scanning transmission electron microscopy (STEM) in high-angle annular dark field (HAADF) mode.…”
Section: Introductionmentioning
confidence: 99%
“…Due to confinement at the surface of the substrate, both diffusion on the free surface of the film and at the interface with the substrate can participate in the process. Mechanisms and kinetics of dewetting depend on the nature of both film and substrate (crystalline or amorphous) as well as on the annealing atmosphere; they have been studied in particular for films of the platinum group and of noble metals . Yet, in the case of complex polycrystalline films on amorphous flat substrates, recent studies using various in situ and real‐time measurement imaging techniques have shed light on the major role played by grains in the kinetics of dewetting and in the evolution of the coverage/density of objects and holes .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms and kinetics of dewetting depend on the nature of both film and substrate (crystalline or amorphous) as well as on the annealing atmosphere; they have been studied in particular for films of the platinum group and of noble metals . Yet, in the case of complex polycrystalline films on amorphous flat substrates, recent studies using various in situ and real‐time measurement imaging techniques have shed light on the major role played by grains in the kinetics of dewetting and in the evolution of the coverage/density of objects and holes . The particles obtained in such cases have a large size dispersion, while their shapes may vary from faceted truncated spheres to complex worm‐like objects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For biomedical applications in which the control over the morphology is fundamental for the regulation of the balance between cytotoxicity and antimicrobial properties, the controlled dewetting of Ag thin films allowed some to obtain non-cytotoxic structures presenting antimicrobial properties [94,95]. The dewetting of thin films is a thermally-driven process, which, performed at a temperature below the melting point, leads to the evolvement of the surface morphology up to the formation of separate droplets/3D islands [96][97][98]. The dewetting process was carried out in air for 1 h with temperature varying from 200 to 600 • C on Ag thin films deposited by means of IJD technology onto silica substrate [99].…”
Section: Antibacterial Thin Films By Pedmentioning
confidence: 99%